Bahay [videorecording] houses in the Philippines through the years.
This is the story of the Filipino house... how changes in its style and design reflect the transformation in Filipino ways and traditions through the centuries and how basic facets of its structure that have remained the same illustrate the timelessness and permanence of certain values and more that are the foundations of Filipino life.